2002
DOI: 10.1063/1.1481986
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally modified chirped pulse generation of sustained shock waves

Abstract: A method is described for generating shock waves with 10–20 ps risetime followed by >200 ps constant pressure, using spectrally modified (clipped) chirped laser pulses. The degree of spectral clipping alters the chirped pulse temporal intensity profile and thereby the time-dependent pressure (tunable via pulse energy) generated in bare and nitrocellulose-coated Al thin films. The method is implementable in common chirped amplified lasers, and allows synchronous probing with a <200 fs pulse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 20 publications
0
33
1
Order By: Relevance
“…Details of the technique used for the free surface measurements were published by Bolme et al 15 and details for the spectral shaping of the shock drive pulse were published by McGrane et al 16 For these experiments, the laser was focused through the glass to an ϳ100 m spot at the aluminum film to generate the shock. Since the energy of the drive pulse was Gaussian shaped across the spatial dimension, we present data from an approximately 5 m spatial region in the center of the shock, where the shock was traveling normal to the surface of the aluminum.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Details of the technique used for the free surface measurements were published by Bolme et al 15 and details for the spectral shaping of the shock drive pulse were published by McGrane et al 16 For these experiments, the laser was focused through the glass to an ϳ100 m spot at the aluminum film to generate the shock. Since the energy of the drive pulse was Gaussian shaped across the spatial dimension, we present data from an approximately 5 m spatial region in the center of the shock, where the shock was traveling normal to the surface of the aluminum.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…McGrane et al reported that the pressure loaded by roughly same intensity was over 100 GPa. 14) However in this past study, the glass substrate was put on the target specimen in order to confine the ablation pressure. Because we irradiated the femtosecond laser in air and the ablation pressure was not confined, the pressure was much lower than the McGrane et al.…”
Section: Resultsmentioning
confidence: 99%
“…But in order to achieve our goal of seeing shock-induced chemistry in real time, we must increase the shock pressure, probably to the >10 GPa range, and combine it with flashpreheating. Studies by the David Moore group show how such high-pressure shocks are generated [11], but this requires more pulse energy than the 0.5 mJ available with our laser. Consequently, we plan to build an additional laser amplifier.…”
Section: Discussionmentioning
confidence: 99%
“…We studied data from the David Moore group at LANL, who used a similar apparatus to study shocks with ultrafast interferometry as a function of drive pulse intensity and layer thickness [10,11]. Using this data, we estimated 13 GPa in Au, dropping to 1.2 GPa in the monolayer due to the poor impedance match.…”
Section: Discussionmentioning
confidence: 99%